A cross-sectional study of soft tissue facial morphometry in children of West Bengal - Badruddin A Bazmi; Shabnam Zahir (Wolters Kluwer Medknow Publications, 2013)
Context: Facial analysis is the first step in the evaluation of patients with orthodontic, cosmetic, or reconstructive procedures of the face, and one of the most important components of orthodontic diagnosis and treatment planning. It is a well-established fact that human faces differ from one another on the basis of race and ethnicity. The study will provide the aesthetic guidelines to assess the facial discrepancy in Bengali children to develop a proper treatment plan. Aims: To find out the mean values for selective linear measurements on the facial soft tissue of Bengali children, to demonstrate gender differences in the measurements. Materials and Methods: A cross-sectional study was done on 250 Bengali children of 6-14 years age, by measuring certain identified facial landmarks using a digital caliper. Statistical Analysis Used: Analytical statistical method with the help of student's t-test was used to determine mean values, standard deviation, and gender differences in the measurements using SPSS version 11.0. Results: In 6-8 years age group, male's average inter-endocanthion distance was significantly higher than that of females ( P < 0.05), whereas in 12-14 years age group, the same parameter for females was significantly higher than that of males ( P < 0.001). In 9-11 years age group, the average distance of exocanthion to exocanthion was higher for males compared to females, but the difference was not significant at 5% level ( P > 0.05), though for 87% of cases, it was significant ( P = 0.13). Total facial height for male subject was significantly high compared to that of females ( P < 0.001) in 12-14 years age group. Conclusions: The study will provide the aesthetic guidelines to assess the facial discrepancy in Bengali children and provide a proper treatment plan through a simple and economically reasonable soft tissue analysis method.